2016
DOI: 10.1017/ice.2016.271
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ICD-9-CM Diagnosis Codes for Surgical Site Infection and Noninfectious Wound Complications After Mastectomy

Abstract: Background Few studies have validated ICD-9-CM diagnosis codes for surgical site infection (SSI), and none have validated coding for noninfectious wound complications after mastectomy. Objectives To determine the accuracy of ICD-9-CM diagnosis codes in administrative health insurer claims data to identify SSI and noninfectious wound complications, including hematoma, seroma, fat and tissue necrosis, and dehiscence, after mastectomy. Methods We reviewed medical records for 275 randomly selected women who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…14,15 Briefly, SSIs recorded during the first 30 days after surgical procedures were identified using ICD-9-CM diagnosis codes from encounters in the State Inpatient Databases and State Ambulatory Surgery Databases. 16 Prior work 17,18 in this area has suggested that use of these codes has sensitivity similar to that of routine clinical surveillance for detecting complex SSI, but a lower positive predictive value. We censored the observation period to avoid misclassification of SSIs after a subsequent surgery using the NHSN procedure list, as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Briefly, SSIs recorded during the first 30 days after surgical procedures were identified using ICD-9-CM diagnosis codes from encounters in the State Inpatient Databases and State Ambulatory Surgery Databases. 16 Prior work 17,18 in this area has suggested that use of these codes has sensitivity similar to that of routine clinical surveillance for detecting complex SSI, but a lower positive predictive value. We censored the observation period to avoid misclassification of SSIs after a subsequent surgery using the NHSN procedure list, as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…1 Unfortunately, ICD-9-CM coding is subject to error and does not always reflect the true level of comorbid and acute illnesses. 2 Little research has been done to determine the accuracy of ICD-9-CM codes to identify multidrug-resistant organism (MDRO) infections.…”
Section: To the Editormentioning
confidence: 99%
“…To the Editor— The International Classification of Diseases, Ninth revision, Clinical Modification (ICD-9-CM) coding system is often used to conduct surveillance for various infections 1 . Unfortunately, ICD-9-CM coding is subject to error and does not always reflect the true level of comorbid and acute illnesses 2 .…”
mentioning
confidence: 99%
“…Na literatura, observa-se que as principais complicações apresentadas pós-mastectomia são infecção 4,9,26 , hematoma 4,27 , seroma 4,5,9,[27][28][29] , deiscência 4,9,27 , necrose 4,27 , sangramento 9 e celulite 27 . O que corrobora com o estudo, o qual também inclui a epidermólise como complicação incidente no pós-operatório de mastectomia.…”
Section: Discussionunclassified